HUMAN RESOURCE PLANNING IN ISLAMIC EDUCATION - M Ihsan Al Fikri; Fahrurroji; Fadhilah; Jamilus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Human resource (HR) planning in Islamic education was a strategic process aimed at ensuring the availability of professional and qualified educators and staff grounded in Islamic values. This article discussed the concept, foundation, principles, scope, and challenges of HR planning in Islamic education using a descriptive literature-based approach. The analysis revealed that HR planning in Islamic education not only involved technical and administrative aspects but also embraced spiritual and moral dimensions, including the principles of monotheism (tauhid), justice, trust (amanah), honesty, sincerity, and consultation (shura). Effective implementation improves educational quality, institutional efficiency, and the development of Islamic character. However, challenges remain, such as the limited number of competent educators, financial constraints, and weak integrated HR management systems. Value-based HR planning.